Informal Trade and Nepal-India Economic Cooperation: Nepalese Perspective - Karmacharya, Binod K. (Economic Journal of Nepal, 2006)
One serious issue of concern in Nepal-India economic relation is the incidence of informal trade along long open border between the two countries. This paper dwells upon the various aspects of informal trade (their extent, underlying causes and adverse implications to Nepal) followed by discussion on the measures that need to be taken to curb and formalize them.Economic Journal of Nepal Vol.29(2) 2006 pp.77-84